An Optimum Design and Economic Analysis of Renewable PV-Standalone Power Plant for Electric Vehicle Charging Station in Indonesia. Issue 1 (March 2021) - Apribowo, C H B; Nizam, M; Anwar, M; Arifin, Z; Tjahjana, D D D P; Iftadi, I; Inayati,; Ramelan, A; Falich, M N
Abstract: Electric vehicles have recently been increasing in popularity and market demand which can be used as a key indicator for the future due to climate change and global warming so that CO 2 emission reductions are needed. In addition to environmental factors which are the main motivation for the increase in electric vehicles, this type of transportation reduces dependence on fossil fuels and contributes a lot to energy independence. The increasing popularity of electric vehicles requires a country to build a charging station for the community in the future, including Indonesia. For that reason, this study was made to obtain the most optimal PV-standalone design as a charging station with the economic analysis. Semarang city is the location of choice because of the potential for strategic resources and is one of the cities with the highest number of vehicles. The result is that 23.2kW PV, 9kW converter, and 40kWh battery are the most optimal for charging stations in the city of Semarang with 10 electric cars every day, with a total daily load of 88kWh/day.